Losartan sensitizes selectively prostate cancer cell to ionizing radiation - Yazdannejat, H; Hosseinimehr, S J; Ghasemi, A; Pourfallah, T A; Rafiei, A (Cellular and Molecular Biology, 2016)
Losartan is an angiotensin II receptor (AT-II-R) blocker that is widely used by human for blood pressure regulation. Also, it has antitumor property. In this study, we investigated the radiosensitizing effect of losartan on cellular toxicity induced by ionizing radiation on prostate cancer and non-malignant fibroblast cells. Human prostate cancer (DU-145) and human non-malignant fibroblast cells (HFFF2) were treated with losartan at different concentrations (0.5, 1, 10, 50 and 100 µM) and then these cells were exposed to ionizing radiation. The cell proliferation was determined using MTT assay. Our results showed that losartan exhibited antitumor effect on prostate cancer cells; it was reduced cell survival to 66% at concentration 1 µM. Losartan showed an additive killing effect in combination with ionizing radiation on prostate cancer cell. The cell proliferation was reduced to 54% in the prostate cancer cells treated with losartan at concentration 1 µM in combination with ionizing radiation. Losartan did not exhibit any toxicity on HFFF2 cell. This result shows a promising effect of losartan on enhancement of therapeutic effect of ionizing radiation in patients during therapy.